Long non-coding RNA, a supreme post-transcriptional immune regulator of bacterial or virus-driven immune evolution in teleost - Haridevamuthu, B.; Guru, Ajay; Velayutham, Manikandan; P., Snega Priya; Arshad, Aziz; Arockiaraj, Jesu (Wiley, 2023)
The global aquaculture boom, fuelled by a reduction in wild population and detection of novel viruses, has created a demanding market, hence, there is a pressing need to investigate the immune system of fish, further. As the most diverse community of vertebrates and a central contributor to the progressing global aquaculture market, teleost continues to draw vast scientific interest. Recent breakthroughs in multi-omics technologies have provided a platform to understand the role of long non-coding RNA (lncRNA) in the host immune system during infection. Emerging evidence shows that teleost lncRNA might have a regulatory role in immune responses, mostly through lncRNA–microRNA (miRNA) sponging. Teleost lncRNA shares a functionally active short sequence complement to target the miRNA which is conserved among the several fish species. Recent report suggests that rhabdovirus exploits a lncRNA in teleost and, to dodge the host immune mechanism and negatively regulate the immune system. This observation reveals the essentiality of lncRNA in pathogen-driven immunity in teleost. Reports available on the function of teleost lncRNA are still in early stages and experimental verifications are a limiting factor. Unravelling the lncRNA-mediated immune regulation in fishes could be used against the invading pathogens to strengthen the aquaculture production. This review elaborates on the experimentally identified and functionally characterized lncRNA and its regulatory role in the teleost immune response during infection and pathogen-driven host immune evolution, which could eventually lead to achieving high standards in aquaculture productivity.